Philippine guidelines on periodic health examination (PHEX) effective screening for diseases among apparently healthy Filipinos. (Publications Program, Information, Publication and Public Affairs Office, University of the Philippines Manila, 2004)
It is the first comprehensive evaluation and synthesis of preventive interventions and immunization in our country. It is aimed at promoting the most constructive and cost-efficient use of diagnostic tools in detecting illnesses afflicting our local citizenry.